PESERTA DIDIK DALAM WAWASAN AL-QURAN - Fakhrurrazi, Fakhrurrazi (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2020)
Al-Qur'an is a guide to human life from various aspects ranging from social, economic, worship, education and so forth. There are many in the Qur'an about stories in the process of learning about the prophet such as the story of the prophet Moses meeting with the prophet khaidir, the story of the prophet isa, the story of the yahya prophet, the story of Abraham and the judge Lukmanul enshrined in the Qur'an ' about educating their children to be children who always remember Allah and always remind them not to associate partners with God and order their children to always do good deeds, uphold the truth and be good learners and have good morality. Students are an important component in the process of Islamic education. Students suggest people who participate in the education process.